SYARI’AH: (KONSEP DASAR, URGENSI DAN TUJUANNYA) - Djaenab Djaenab (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Shari'ah is the whole doctrine revealed by Allah Almighty through His Messenger to be a guide in action, in it includes aqidah, rules (law) and morals. Although the definition of shari'a in its development has narrowed the meaning, so it is more identical with the law and fiqh, but basically the three things remain different. Shari'ah which Allah revealed that is burdening human beings demands understanding of reason and ability to execute it. The declared shari'ah does not intend to burden a human being, but has the urgency to release man from hardship (masyaqqah) and to guide him not to indulge his desires. The charged shari'ah contains a purpose to create the benefit of the world and the Hereafter. The benefit can be achieved by maintaining the dharury mashlah that is to maintain religion, soul, mind, wealth and descent. With the maintenance of these six things, then maslahah will be done.